Three-Dimensional Finite Element Numerical Simulation of Cave Block of Underground Dam in Karst Area - DA Mingchang; JIAO Jie; SU Zhengyang (Renmin Zhujiang)
There are many problems in safety management and risk assessment of underground reservoir project in karst area because of the special structure and environment.Taking a typical karst underground reservoir project in southwest China as the research object,this paper establishes the three-dimensional finite element model of its cave block to analyze the variation law of its temperature field,stress field and displacement field under different working conditions.The results show that:the overall deformation of the cave block was small,and the stress level of the cave block was generally within the safe range under various working conditions.There was stress concentration at the local position between the cave block and bedrock,but the overall stress distribution met the requirements of the code.The research results serve as a reference for safety evaluation and risk analysis of underground reservoir projects in karst areas.